МЕТОДИ ОПТИМІЗАЦІЇ - Кушнірчук, Василь Йосипович; Кушнірчук, Володимир Васильович (Видавництво Чернівецького національного університету імені Юрія Федьковича, 2025)
The textbook outlines the basic concepts of the course "Optimization Methods", which the author teaches to students of the Faculty of Mathematics and Informatics. In addition to the theoretical material, the textbook contains practical problems for each chapter. The textbook will be useful for students and anyone who wants to get acquainted with the basic concepts of probability theory.
Keywords: оптимізація; функція мети; критерій; лінійна/нелінійна оптимізація; цілочисельна оптимізація; симплексний метод; багатокритеріальна оптимізація; optimization; objective function; criterion; linear/nonlinear optimization; integer optimization; multicriteria optimization; simplex method